Enhancing dopant diffusion for ultrahigh electrical conductivity and efficient thermoelectric conversion in conjugated polymers - Yoon, Sang Eun; Kang, Yeongkwon; Im, Jaemin; Lee, Jiyun; Lee, Sang Yeon; Park, Jaehong; Gao, Yuan Jun; Jeon, Dohyeon; Son, Ji Yoen; Kim, Jisu; Kousseff, Christina J.; Kim, Taekyeong; et al. (Joule, 2023)
Organic thermoelectric (TE) attracts considerable interest as a next-generation energy conversion technology; however, its practical application is still restricted by low power factors. Herein, we report a generally applicable solvent-combination doping method for improving TE properties of conjugated polymers (CPs). Residual solvents in a ternary solvent enlarged the free volume in the CP films. This beneficial effect boosted both dopant diffusion efficiency and charge carrier density in the doped films, resulting in the remarkable enhancement of electrical conductivity in the CPs. When the doped CP films processed with a ternary solvent were applied to TE devices, excellent power factors were achieved, attributed to a durable Seebeck coefficient along with ultrahigh electrical conductivity.
Keywords: Dopant-diffusion; Electrical conductivity; Metallics; Molecular doping; Organic thermoelectric; Organics; Power factors; Semi-metallic electrical conductivity; Solvent combination; Thermoelectric; conjugated polymers; dopant diffusion; molecular doping; organic thermoelectric; power factor; semi-metallic electrical conductivity; solvent combination